Assessment of cognitive function in bipolar disorder with passive smartphone keystroke metadata: a BiAffect digital phenotyping study - Ajilore, Olusola; Bark, John S.; Demos, Alexander P.; Zulueta, John; Stange, Jonathan; Duffecy, Jennifer; Hussain, Faraz; Langenecker, Scott A.; Nelson, Peter; Ryan, Kelly; McInnis, Melvin G.; Leow, Alex (Frontiers in Psychiatry, 2025)
BackgroundCognitive dysfunction in bipolar disorder persists in the euthymic state and has been shown to be associated with a number of negative sequelae including treatment resistance and increased risk of relapse. There has been recent attention on digital phenotyping and passive sensing through smart, connected devices to probe cognition in real-world settings. BiAffect is a custom-built smartphone keyboard that captures keystroke metadata (‘how you type, not what you type’). In previous studies, our group has demonstrated that BiAffect-derived keystroke metadata is associated with cognitive domains like processing speed. For the present study, we hypothesized that typing metadata would be significantly associated with executive function and planning.Methods18 participants with bipolar disorder and 12 healthy comparison participants from the Prechter Longitudinal Study of Bipolar Disorder at the University of Michigan were provided a mobile phone with a customized keyboard that passively collected keystroke metadata. Participants also completed a neuropsychological battery including the Tower of London task. Irregularities in typing and times to make a move on the Tower of London task were compared using sample and Shannon entropy, respectively.ResultsParticipants with bipolar disorder had significant increases in entropy in typing (p = .005, d = -1.28) and entropy of Tower of London move times (p = .029, d = -.84). Furthermore, typing entropy was significantly associated with irregularity in Tower of London moves in participants (r = .59, p = .006), as well as variability of clinician-rated depressive symptoms and self-rated impulsive actions and feelings.ConclusionsThis pilot study demonstrates that passive, unobtrusive smartphone keystroke metadata can be used to probe cognitive function and dysfunction in bipolar disorder, revealing multi-scalar behavioral features accessible through digital assays